Challenges in implementation of community-based-tourism and homestay post-Covid-19 movement control order (MCO) at Kundasang, Sabah - Dayang Siti Noorafidah Datu Nordin; Normah Abdul Latip; Kasim Mansur; Rosazman Hussin (Malaysia Institute of Planners, 2023)
This article discusses the challenges in implementing the community-based tourism and homestay post covid-19 movement control order (MCO) at Kundasang, Sabah. The spread of the Covid-19 virus has had a significant impact on the community and, at the same time, on tourism activities. The implementation of the MCO, announced by the Prime Minister of Malaysia on March 18, 2020, has led all sectors, including the tourism sector, to stop operating temporarily to curb the virus from continuing to be prevalent among the community. On June 10, 2020, the government implemented the Recovery Movement Control Order (RMCO), allowing all sectors to operate again. However, there is a question of what challenges the tourists face in implementing the post-covid-19 recovery strategy and plan in Kundasang. The primary approach to this study is qualitative, based on primary and secondary data sources. The preliminary data is used through in-depth interviews while in the field. Secondary data is from journal articles, academic reference books and newspaper news widely used in this writing. The results of this study found that there were challenges facing the community, especially homestay operators, where the challenges they faced were different in implementing the post-covid19 tourism recovery strategy in Kundasang, Sabah.